Altering starch branching enzymes in wheat generates high-amylose starch with novel molecular structure and functional properties. (July 2019) - Li, Haiteng; Dhital, Sushil; Slade, Ann J.; Yu, Wenwen; Gilbert, Robert G.; Gidley, Michael J.
Abstract: Starch that escapes intestinal digestion (resistant starch, RS) is non-glycaemic and considered as dietary fibre. In planta increase of amylose content is a promising approach to make starch resistant to enzyme digestion. Compared to maize, little is known on the effect of amylose content at different length scales of high-amylose wheat (HAW) starch structure and properties. A range of starches with 37%–93% apparent amylose content (AM) were isolated from high-amylose bread wheat produced through non-transgenic breeding altering starch branching enzymes (SBE IIa and IIb). Compared to mutations only in SBEIIa, mutations of both SBE IIa and IIb resulted in higher amylose content with significantly increased proportion of long amylopectin chains (degree of polymerization ≳ 20) and amylose chains. The modified starch molecular structure has significant correlations with starch supramolecular structure and functionality. Compared with wild-type starch, HAW starches showed distinct granular morphology and crystalline pattern with a higher fraction of B-type and V-type polymorph (amylose complex). The peak temperature (Tp ) was higher but the onset temperature (To ) of gelatinization was not greatly raised (<3 °C) by the mutations. Pasting behaviour of HAW starches (AM<50%) remained similar to wild type, but was greatly reduced at higher AM levels. The data suggest that, depending on food processing condition requirements, different functional and RS properties can be selected based on wheat starch AM content. Graphical abstract: Image 1 Highlights: Mutations of both SBE IIa and IIb in wheat resulted in highest amylose content. Wheat high-amylose starch (HAS) structural features similar to other cereal HAS. Wheat HAS contained a higher proportion of both B-type and V-type polymorph. Gelatinization onset temperature only has minor changes (<3 °C) in wheat HAS.